A systematic review of pragmatic language interventions for children with autism spectrum disorder. - Lauren Parsons; Reinie Cordier; Natalie Munro; Annette Joosten; Renée Speyer (PLoS ONE)
There is a need for evidence based interventions for children with autism spectrum disorder (ASD) to limit the life-long, psychosocial impact of pragmatic language impairments. This systematic review identified 22 studies reporting on 20 pragmatic language interventions for children with ASD aged 0-18 years. The characteristics of each study, components of the interventions, and the methodological quality of each study were reviewed. Meta-analysis was conducted to assess the effectiveness of 15 interventions. Results revealed some promising approaches, indicating that active inclusion of the child and parent in the intervention was a significant mediator of intervention effect. Participant age, therapy setting or modality were not significant mediators between the interventions and measures of pragmatic language. The long-term effects of these interventions and the generalisation of learning to new contexts is largely unknown. Implications for clinical practice and directions for future research are discussed.